Main historical stages in the field of physical culture and sports management (analysis of the past, present, future forecast) - N. V. Filonenko (Путеводитель предпринимателя)
The article substantiates the need for a theoretical analysis of the main historical stages in the field of industrial management. Attention is focused on the military–applied and professionally applied orientation of physical culture, which has been preserved for more than a century, including the present. In connection with the identified shortcomings, it is proposed to increase the number of hours for teaching basic military training in the form of a separate subject in grades 5–11, as was the case in Soviet secondary schools. Also, approval at the legislative level of the introduction of communicative and digital forms of industrial gymnastics in all organizations, regardless of the types of activities and organizational and legal forms of ownership, as it was during the existence of the Soviet Union. A structural unit of educational organizations is a boarding school with a sports profile, 24 hours a day, accepting children from the age of 7 at the expense of budget funding, as was the case in the USSR. This will make it possible to prepare a reserve for the national teams of the constituent entities of the Russian Federation and the country in aesthetic sports, the specificity of which is early specialization. The resulting socio–economic and political circumstances in the early 1990s prompted the emergence of industry–specific sports management and many innovations. But time shows the need to study the past to avoid shortcomings in the present, to use the positive experience of continuity from the Soviet management of physical culture and sports for its application in modern Russia.